Lie. kū́nas - Karaliūnas, Simas (Baltistica, 1982)
Lith. kū́nas “body”The cognates of Lith. kū́nas “body” and Latv. kûnis (kи̃пе, kũņа) “body; chrysalis; caterpillar of a butterfly; bee pupae” are supposed to be Lith. kūпа “carrion”, pa-kū́nė “sore, furuncle; upper lamella, a layer under the roots”, Latv. kипа “wart, excrescence”, kunis “bottom of a sheaf” and others. Lith. kū́nas, kūпа may represent substantivized forms of the adjective Latv. kûns“round, obese, stout”, while Latv. kûnis, kũņа, kūne seem to be derivatives of the suffixes *-o-*-ā-, *-ē-.
Keywords: lithuanian; body; etymology